2022
DOI: 10.3390/metabo13010045
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Mycotoxin Alternariol with Cytochrome P450 Enzymes and OATP Transporters

Abstract: Alternariol (AOH) is an emerging mycotoxin produced by Alternaria strains. The acute toxicity of the mycotoxin is low; however, chronic exposure to AOH may result in the development of endocrine disruptor and/or carcinogenic effects. The toxicokinetic properties of AOH have barely been characterized. Therefore, in this study, we aimed to investigate its interactions with CYP (1A2, 2C9, 2C19, 2D6, and 3A4) enzymes and OATP (1A2, 1B1, 1B3, and 2B1) transporters employing in vitro enzyme assays and OATP overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…AOH have been reported to enhance the expression of CYP1A cytochrome in human cells of different tissue origin, especially in esophageal cells [ 44 , 45 ]. Another recent in vitro study has shown that AOH is a potent inhibitor of CYP1A2, CYP2C9, but not of CYP2C19, 2D6, and 3A4 [ 46 ]. The computational model predicted that AOH had high probability to be substrate for Cyp1A1, Cyp1A2 but also for Cyp2C12, Cyp1A6, Cyp2B6, Cyp2C, and Cyp2C9 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…AOH have been reported to enhance the expression of CYP1A cytochrome in human cells of different tissue origin, especially in esophageal cells [ 44 , 45 ]. Another recent in vitro study has shown that AOH is a potent inhibitor of CYP1A2, CYP2C9, but not of CYP2C19, 2D6, and 3A4 [ 46 ]. The computational model predicted that AOH had high probability to be substrate for Cyp1A1, Cyp1A2 but also for Cyp2C12, Cyp1A6, Cyp2B6, Cyp2C, and Cyp2C9 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…A rapid and highly sensitive method was validated for the quantification of probe substrates in dog liver microsomes (DLMs) following the guidelines for bioanalytical method validation [37]. The acetonitrile protein precipitation method was applied to develop a sensitive UPLC-MS/MS method for determining the specific metabolites of each CYP450 probe substrate [38][39][40][41]. As shown in Figure 1, there were no interfering peaks detected in the blank sample at the retention time of the target compounds and internal standard.…”
Section: Methods Validationmentioning
confidence: 99%
“…Examples of waste near to generation: aa felled tree; bfallen leaves But if the waste will not be utilised as soon as possible, it will be a culture medium for different microbes, fungi and moulds. The last ones produce carcinogenic, teratogenic, immunotoxic mycotoxins such as ochratoxin A [10], aflatoxins [10], deoxynivalenol [11], fumonisin [12]. In natural conditions, such mediums are distributed, which cause low concentration of pathogens.…”
Section: Biowaste Managementmentioning
confidence: 99%